2009
DOI: 10.1007/s11270-009-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamides Leach from Sandy Loam Soils Under Common Agricultural Practice

Abstract: Sulfonamide antibiotics can enter agricultural soils by fertilisation with contaminated manure. While only rough estimations on the extent of such applications exist, this pathway results in trace level contamination of groundwater. Therefore, we studied the transport of three sulfonamides in leachates from field lysimeters after application of a sulfonamide-contaminated liquid manure. In a 3-year period, the sulfonamides were determined in 64% to 70% of all leachate samples at concentrations between 0.08 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 32 publications
(44 reference statements)
1
60
0
Order By: Relevance
“…Leaching is the vertical percolation of materials into the groundwater that preferentially occurs in a particular flow path and plays more of a role with antibiotics that are hydrophilic and/or not tightly sorbed to the soil particles (Jechalke et al, 2014). Therefore, antibiotics that are hydrophobic and/or interacting strongly with the soil particles may not leach beyond the surface soil (Aust et al, 2010;Ostermann et al, 2013). Hamscher, Abu-Quare, Sczesny, Höper, and Nau (2000) discovered that 9.5 μg/kg chlortetracycline was recovered in 10-cm topsoil samples received from farms after the second day of animal slurry application and a decreased concentration of about 0.7 μg/kg in soil samples collected at a depth below 80 cm.…”
Section: Complete Biodegradation or Alteration Of Antibiotics Dischargedmentioning
confidence: 99%
“…Leaching is the vertical percolation of materials into the groundwater that preferentially occurs in a particular flow path and plays more of a role with antibiotics that are hydrophilic and/or not tightly sorbed to the soil particles (Jechalke et al, 2014). Therefore, antibiotics that are hydrophobic and/or interacting strongly with the soil particles may not leach beyond the surface soil (Aust et al, 2010;Ostermann et al, 2013). Hamscher, Abu-Quare, Sczesny, Höper, and Nau (2000) discovered that 9.5 μg/kg chlortetracycline was recovered in 10-cm topsoil samples received from farms after the second day of animal slurry application and a decreased concentration of about 0.7 μg/kg in soil samples collected at a depth below 80 cm.…”
Section: Complete Biodegradation or Alteration Of Antibiotics Dischargedmentioning
confidence: 99%
“…Wehrhan et al (2007) observed that kinetic sorption was the most relevant process for the removal of SDZ at the laboratory scale. Within a larger scale of lysimeter studies, Aust et al (2010) observed an increased leaching potential of sulfonamides after their application with manure. However, Aust et al (2010) did not investigate the transformation processes of SDZ, nor did they use numerical models to analyze or predict the long-term and large-scale fate of sulfonamides.…”
Section: Introductionmentioning
confidence: 99%
“…Within a larger scale of lysimeter studies, Aust et al (2010) observed an increased leaching potential of sulfonamides after their application with manure. However, Aust et al (2010) did not investigate the transformation processes of SDZ, nor did they use numerical models to analyze or predict the long-term and large-scale fate of sulfonamides. Currently, long-term and largescale field studies that investigate the leaching potential and biodegradation of sulfonamides, such as SDZ, using undisturbed natural soils and under variable hydrological conditions, are still not available.…”
Section: Introductionmentioning
confidence: 99%
“…Leachate 0.78 μg L −1 Blackwell et al (2007) Leachate 95-97% Unold et al (2009) Leachate 0.08 to 56.7 μg L −1Aust et al (2010) …”
mentioning
confidence: 99%